Tindak Tutur Komisif dan Direktif dalam Promosi TikTok Berbahasa Arab untuk ASP Pariwisata: Tindakan Wacana Komissif dan Direktif dalam Promosi Pariwisata Berbahasa Arab di TikTok - Rachma Nurhaliza; Mia Nurmala; Sari Tasya Mahrima (Language Development Center, 2026)
Background: The rapid growth of the Middle Eastern tourist market demands advanced communication skills from tourism practitioners. However, current teaching materials for Arabic for Specific Purposes (ASP) in Tourism are often limited to conventional transactional offline scenarios, which are increasingly less relevant to modern digital promotion needs. Purpose: This study explores the pragmatic functions of speech acts in Arabic tourism promotional discourse on TikTok and examines their pedagogical implications for developing adaptive, industry-relevant ASP materials. Method: Employing Krippendorff's qualitative content analysis, this study analyzed 61 speech units extracted from five purposively selected travel-agency TikTok accounts with high engagement and explicit Arabic promotional content targeting Middle Eastern tourists. Out of 124 transcribed units 61 relevant commissive and directive units were analyzed. The data were gathered through documentation and coded based on Searle and Leech's pragmatic functional schemes, focusing specifically on persuasive strategies within digital discourse. Results and Discussion: The findings reveal a clear predominance of commissive speech acts (77%) over directive speech acts (23%). This suggests that digital tourism marketing discourse tends to prioritize trust-building through promises and guarantees over direct instruction. Linguistically, this persuasion is realized through the efficient use of ḥadhfu al-mubtada’ (subject omission) structures, the integration of digital technical lexicons, and the strategic code-switching into the ‘ammiyyah (colloquial) variety to foster emotional closeness. Conclusions and Implications: This study highlights the necessity of updating current educational resources. It recommends reorienting the ASP Tourism curriculum toward a functional-pragmatic approach that integrates digital copywriting skills, technological literacy, and sociolinguistic flexibility, ultimately preparing competent tourism graduates for the digital era.